Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.5812/ajnpp.12514
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Cellphone Overuse and Depression Among Medical College Students in Hamadan, West of Iran

Abstract: Background: Its contact the main reason for the use of mobile phones is especially students living in dormitories. As well as students to communicate in cyber space than in real space of communication are interested, this can threaten their mental health. Objectives: The current study aimed at exploring the amount of mobile phone overuse and determining the association between mobile phone overuse and depression among medical college students in Hamadan, West of Iran. Methods: The current cross sectional study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 17 publications
(12 reference statements)
0
5
0
Order By: Relevance
“…Investigating the expertise of the corresponding authors of the 47 selected articles showed that the problematic use of mobile phone has attracted the attention of various study fields including medical sciences,[ 27 ] safety engineering,[ 28 29 ] curriculum planning,[ 30 31 ] psychiatry,[ 32 33 ] social sciences,[ 34 ] educational technology,[ 35 ] communications,[ 36 37 ] educational management,[ 38 39 ] health education,[ 40 41 42 43 44 45 ] counseling,[ 46 47 ] nursing,[ 48 49 50 51 52 53 ] epidemiology,[ 54 55 ] and psychology. [ 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 ] The findings also showed that problematic use of mobile phone was investigated the most by psychologists because they constituted up to half of the corresponding authors.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Investigating the expertise of the corresponding authors of the 47 selected articles showed that the problematic use of mobile phone has attracted the attention of various study fields including medical sciences,[ 27 ] safety engineering,[ 28 29 ] curriculum planning,[ 30 31 ] psychiatry,[ 32 33 ] social sciences,[ 34 ] educational technology,[ 35 ] communications,[ 36 37 ] educational management,[ 38 39 ] health education,[ 40 41 42 43 44 45 ] counseling,[ 46 47 ] nursing,[ 48 49 50 51 52 53 ] epidemiology,[ 54 55 ] and psychology. [ 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 ] The findings also showed that problematic use of mobile phone was investigated the most by psychologists because they constituted up to half of the corresponding authors.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous terms such as addiction, dependency, overuse, problematic use, high use, and excessive use were employed to address the problematic use of mobile phones [ Table 1 ]. Out of the 47 articles in the current review, the term “addiction” was used in 18 studies (38.3%),[ 30 31 32 34 36 37 42 48 53 56 57 61 62 63 66 68 70 71 ] “dependency” was used in 11 studies (23.4%),[ 35 39 41 42 49 50 51 60 64 65 69 ] “overuse” in nine studies (19.1%),[ 27 28 29 40 45 46 47 55 58 ] “problematic use” in five (10.6%) of the studied papers,[ 59 63 67 72 73 ] “high use” appeared in three studies (6.4%),[ 33 38 52 ] and “excessive use” appeared in one study (2.1%). [ 44 ] It should be noted that these reported percentages are based on the terms used in the title, or in the abstract if not mentioned in the title.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations